(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2016)
Overview scientific approaches to the specific functioning of integrated marketing communications at point of sale; described five major influence over buyers in the retail trade network; results of research and analyzes the effectiveness of the impact of integrated marketing communications in the retail trade network shoes «Chobitok».